Stakeholders' sustainability reporting perceptions - An example from wood processing industry - Björk, Laura (2024)
This thesis aims to understand stakeholders' perceptions on the importance of various sustainability aspects in the wood processing industry, with a focus on differences among stakeholder groups. A stakeholder survey based on double materiality assessment was conducted, targeting the organization's personnel and key customers. The analysis involved comparing measures of central tendency and employing both Welch's and Student's t-tests. Results indicated that the most important topics, based on mean values, were consumers and end-users, business conduct, workers in the value chain, and the organization's own workforce. The results also indicated that stakeholder perceptions are not always uniform, highlighting the need to directly engage stakeholders rather than relying on assumptions. For the target organization, this thesis provides comprehensive insights into stakeholders' perceptions of CSRD-related sustainability issues, supporting the double materiality assessment process. The study also illustrates the advantages and limitations of survey research in double materiality assessment.